Intraoperative measurement of femoral antetorsion using the anterior cortical angle method: a novel use for smartphones. Issue 1 (19th October 2012) - Hawi, Nael; Kabbani, Abdul‐Rahman; O'Loughlin, Padhraig; Krettek, Christian; Citak, Musa; Liodakis, Emmanouil
Abstract Background Malrotation after femoral nailing is a common problem, yet estimation of the correct rotation during nailing remains a technical challenge. In the current study, a novel technique was developed for determining femoral antetorsion, the anterior cortical angle (ACA) method. The ACA is the angle between a line along the anterior aspect of the femoral neck and the posterior condylar line of the distal femur. The principal advantage of this method is that it facilitates intra‐operative assessment of femoral antetorsion by utilizing the positional technology integrated in smartphones. This measurement is directly comparable to measurements made using computed tomography (CT) scans. The objective of the current study was to investigate the possibility and to validate the feasibility and accuracy of the new method and compare the results obtained with the traditional methods of antetorsion estimation via CT and surgical navigation technology. Methods Twelve cadaveric femora were used. Femoral antetorsion was measured with the ACA method, using a smartphone with integrated gyroscope (Apple IPhone, Cupertino, CA, USA) and by a conventional navigated technique (Brainlab, Feldkirchen, Germany). Subsequently, all femora underwent CT scanning to measure their respective antetorsion via the ACA and the method of Jend (1986). Next, a mid‐diaphyseal osteotomy was performed and the distal fragment was rotated and were adjusted to 10–15° using ACA by smartphone. All measurements were repeated with this new position of the femoral fragments. Results Both radiological measurements according ACA and Jend (1986) demonstrated a statistically significant correlation (intact femur, r = 0.773, p = 0.003; after fixation, r = 0.898, p < 0.001). Comparing the measurements derived from the ACA, as analysed on CT images, and that gleaned from the experimental use of the same method with the smartphone, a statistically significant correlation was also demonstrated (intact femur, r = 0.826, p = 0.001; after fixation, r = 0.932, p < 0.001). Comparing the navigation system and the ACA measured by smartphone there was, on intact femora, a fair correlation without statistical significance and after fixation a good correlation with statistical significance (intact femur, r = 0.467, p = 0.126; after fixation, r = 0.869, p = 0.001). Conclusions The ACA method generated acceptable results and could contribute to improving the results of femoral nailing. The use of this device in a real clinical setting is necessary to truly elucidate its utility. Copyright © 2012 John Wiley & Sons, Ltd.